2017
DOI: 10.1001/jamaoto.2017.1068
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hearing Loss Among Children 9 to 11 Years Old

Abstract: Within this cohort study in the Netherlands, 7.8% of the children ages 9 to 11 years had low-frequency or high-frequency HL of at least 16 dB HL in 1 or both ears. A history of recurrent acute otitis media and lower maternal education seem to be independent risk factors for presumed SNHL in early childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 32 publications
(79 reference statements)
0
46
0
1
Order By: Relevance
“… 46 The high prevalence found herein agrees with the studies that indicate that the prevalence of hearing loss is higher in low- and intermediate-income countries, 47 and indicate socioeconomic factors associated with loss. 6 8 11 14 42 When investigating ear, nose and throat morbidities in school-age individuals in India, there was a significant association between the maternal education level and the search for health services directed to school-age individuals. 37 Herein no specific analysis was performed on schooling, however the education level of the head of household was considered in the economic evaluation proposed by the ABEP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 46 The high prevalence found herein agrees with the studies that indicate that the prevalence of hearing loss is higher in low- and intermediate-income countries, 47 and indicate socioeconomic factors associated with loss. 6 8 11 14 42 When investigating ear, nose and throat morbidities in school-age individuals in India, there was a significant association between the maternal education level and the search for health services directed to school-age individuals. 37 Herein no specific analysis was performed on schooling, however the education level of the head of household was considered in the economic evaluation proposed by the ABEP.…”
Section: Discussionmentioning
confidence: 99%
“…10 Studies indicate an effect of social and economic conditions on the prevalence of hearing loss in school-age individuals, such as low socioeconomic levels, 11,12 income, 6,8 education levels, 13 and low maternal education level. 14 More than 5% of the world population -466 million peoplepresent incapacitating hearing loss (432 million adults and 34 million children). It is estimated that, until 2050, more than 900 million peopleequivalent to 1 out of 10 peoplewill suffer incapacitating hearing loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otitis media is a very common and costly disease in young children that can cause hearing loss and further lead to speech and reading difficulties (Cai & McPherson, ; Carroll & Breadmore, ; Khavarghazalani, Farahani, Emadi, & Hosseni Dastgerdi, ; le Clercq et al, ). Known risk factors for otitis media include young age, lack of breastfeeding, allergies, upper respiratory infection, second‐hand smoke, low social status, daycare attendance, multiple siblings, and family history (Brennan‐Jones et al, ; Y. Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…There were also limitations. Like other population studies,2 25 we lacked bone conduction audiometry owing to the field logistics of a ‘whole participant’ assessment, with hearing just one of multiple health domains. However, our sensitivity analyses indicated that middle ear status likely had little influence (online supplementary figure S1 and table S2).…”
Section: Discussionmentioning
confidence: 99%